Autochthonous Bacillus subtilis and Enterococcus faecalis improved liver health, immune response, mucosal microbiota and red-head disease resistance of yellow drum (Nibea albiflora). Issue 134 (March 2023) - Ding, Xi-Yue; Wei, Cheng-Ye; Liu, Zi-Yan; Yang, Hong-Ling; Han, Fang; Sun, Yun-Zhang
Abstract: Yellow drum ( Nibea albiflora ), a commercially important fish species in the coastal regions of southeast China, is highly susceptible to red-head disease caused by Vibrio harveyi B0003. Probiotics have been shown to enhance disease resistance in fish, but whether commensal probiotics could improve of the resistance to red-head disease in yellow drum and possible mechanisms has yet not been reported. A six-week feeding trial was conducted to investigate the red-head disease resistance potentials of five probiotic candidates ( Bacillus megaterium B1M2, B. subtilis B0E9, Enterococcus faecalis AT5, B. velezensis DM5 and B. siamensis B0E14), and the liver health, serum and skin immunities, gut and skin mucosal microbiota of yellow drum were determined to illustrate the possible mechanisms. The results showed that autochthonous B. subtilis B0E9 and E. faecalis AT5 (particularly E. faecalis AT5, P < 0.05) effectively improved red-head disease resistance in yellow drum. Furthermore, B. subtilis B0E9 and E. faecalis AT5 (particularly E. faecalis AT5) efficiently improve liver health by improving liver morphology and decreasing serum glutamic oxaloacetic transaminase and glutamic propylic transaminase activities pre and post challenged with V. harveyi B0003 ( P < 0.05). B. subtilis B0E9 and E. faecalis AT5 led to significant improvement ( P < 0.05) in the serum complement 3 content (un-detected after challenged with V. harveyi B0003), lysozyme activity and skin mucosal immunity (such as IL-6, IL-10 and lysozyme expression) pre and post challenged with V. harveyi B0003, which was generally consistent with the cumulative mortality after challenged with V. harveyi B0003. This induced activations of serum and skin mucosal immunities were consistent with the microbiota data showing that B. subtilis B0E9 and E. faecalis AT5 modulated the overall structure of intestinal and skin mucosal microbiota, and in particular, the relative abundance of potentially pathogenic Achromobacter decreased while beneficial Streptococcus, Rothia, and Lactobacillus increased in fish fed with B. subtilis B0E9 and E. faecalis AT5. Overall, autochthonous B. subtilis B0E9 and E. faecalis AT5 (particularly E. faecalis AT5) can improve liver health, serum and skin immunities (especially up-regulated lysozyme activity and inflammation-related genes expression), positively shape gut and skin mucosal microbiota, and enhance red-head disease resistance of yellow drum. Highlights: Autochthonous probiotic E. faecalis AT5 and B. subtilis B0E9 improved red-head disease resistance. Commensals improve liver health, mucosal immunity and microbiota of yellow drum. Lysozyme activity may serve as a biomarker for assessing red-head disease resistance.